The effect of hormone concentration towards callus induction of different varieties of paddy / Mohamad Haziq Izzuddin Che Ali - Che Ali, Mohamad Haziq Izzuddin (Faculty of Plantation and Agrotechnology, 2019)
Rice is one of the major crops in Malaysia and important as a staple food of the people in this country. The current rice self-sufficiency level (SSL) in Malaysia is only fulfilling 73% of the target. Currently, the major concern is to improve our paddy production. One of the advantages of tissue culture is can rapidly produce the number of seedling and can improve the production of rice. This research was conducted to study the effectiveness combination of hormone for callus induction on different varieties of paddy which are MR219, MR220 and MR297. The hormone concentration volume of 2,4D are fix at 3.0mgL–1 and NAA there are three combinations of NAA concentration which are 1.0mgL–1, 1.5mgL–1, and 2.0gmL–1. The higher percentages of callus induction at concentration 3.0mgL–1 of 2,4D and 1.0mgL–1 of NAA are MR219 rice variety. At concentration 3.0mgL–1 of 2,4D and 1.5mgL–1 of NAA, the higher of callus induction are MR220 rice variety. Result recorded, the higher of callus induction at concentration 3.0mgL–1 of 2,4D and 2.0mgL–1 of NAA are MR219 rice variety. From this study, MR297 rice variety can be classified as intolerant variety in the three different concentrations and not suitable for callus growth.